2016
DOI: 10.1093/asj/sjw171
|View full text |Cite|
|
Sign up to set email alerts
|

The Modern Polyurethane-Coated Implant in Breast Augmentation: Long-Term Clinical Experience

Abstract: 3 Therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Approximately 50 years ago [ 24 ], an implant with a polyurethane (PU) foam coating was reported with the aim to prevent the risk of CC associated with silicone breast implants [ 25 ]. Thereafter, textured (TE) surfaces have been developed to mimic the shape and the benefits of the PU foam, and several studies have indicated that PU implants have a lower incidence of CC [ 17 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. Furthermore, two studies have suggested that PU implants are associated with a lower incidence of CC in case PMRT is delivered [ 32 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 50 years ago [ 24 ], an implant with a polyurethane (PU) foam coating was reported with the aim to prevent the risk of CC associated with silicone breast implants [ 25 ]. Thereafter, textured (TE) surfaces have been developed to mimic the shape and the benefits of the PU foam, and several studies have indicated that PU implants have a lower incidence of CC [ 17 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. Furthermore, two studies have suggested that PU implants are associated with a lower incidence of CC in case PMRT is delivered [ 32 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the “The Modern Polyurethane-Coated Implant in Breast Augmentation: Long-Term Clinical Experience” 1 would like to thank Dr Frame for his Commentary 2 on our paper and for giving us the chance to highlight once more the results of the study.…”
mentioning
confidence: 99%
“…Obviously, the level of evidence of a retrospective study is not comparable to that of a randomized controlled trial, but that was explicitly stated on the first page, where this study is classified as “level 3” according to the classification for levels of evidence for clinical studies. 1 …”
mentioning
confidence: 99%
See 2 more Smart Citations